Synthesis and Characterization of HS, X and HS + X Type Zeolites from Kaolin and the Study of Their Ion Exchange Capacity for Cu2+, Ni2+ and Co2+ - KHATAMIAN, MAASUMEH; DOLATYARI, MAHBOUBEH (Asian Journal of Chemistry, 2010)
HS, X and HS + X type zeolites are synthesized from kaolin clay having a large amount of impurities such as quartz (39 %) by hydrothermal treatment with NaOH in presence of sodium chloride. The zeolites are crystallized under the optimum hydrothermal conditions and characterized by XRD, FT-IR spectroscopy, BET surface area and SEM-EDS methods. The effects of aging time, crystallization time and crystallization temperature in synthesis of these zeolites are also investigated. Cation exchange capacity (CEC) of X, HS and X + HS (mixed crystallized) zeolites for Cu2+, Ni2+ and Co2+ were determined that they act selectively for exchanging of Cu2+ cation. The cation exchange capacity of these zeolites for mentioned cations were increases as follows: X + HS > X > HS. The XRD patterns of cation exchanged zeolites are also investigated.